Pengembangan Inventori Motivasi Belajar Untuk Siswa Sekolah Menengah Kejuruan - Zela Agnesta Widya Santy; Khairul Bariyyah; Laily Tiarani Soejanto (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
The purpose of this research resulted learning motivation inventory for vocational high school students that meet the requirements of validity and reliability, so that it is able to measure the learning motivation of students that would become the guidelines on teacher guidance and counselling in providing tutoring services as well as to arouse the learning motivation of students. This research is the development of research or research and development model of the Borg and Gall, by involving 317 students. The population of this research is the vocational high school students aged 15-19 years. The taking of the sample of this study using cluster random sampling, while the analysis used product moment pearson, cronbach alpha, test for normality and an analysis of the factors. This research resulted learning motivation inventory for vocational high school students consisting of 59 items statement declared valid, has a high level of reliability, data is normally distributed and has 15 correlating factors on each particular item. Thus this study motivation inventory product can be used to identify learning problems of vocational high school students.